REMBANG DAN BUMBANG - I Nengah Muliana (Institut Seni Indonesia Surakarta, 2011)
Basically, this paper aims to describe the motive behind the creation Bumbang made by Rembang. The scope of this paper focuses on Bumbang creation process, which begins by exploring data on family background, education, learning how musicians, both regard as a musician and instrument maker from bamboo material particular. This is done to get an idea of the extent to which it affects the creation motives of Bumbang itself. In this paper also describes the artistry and his works, in order to get a clear description of the things that encourages creative Rembang of Bumbang. That way, I can know what things are, who contributed so Rembang successfully create new gamelan Bumbang named. To obtain the necessary data, the authors use some method such as: observation, interviews, audio visual recordings, as well as in writing, either in the form of books and others. The collected data were analyzed using the theory proposed by Abraham Maslow who said that the motive for someone doing the activity is to meet their needs.Key words : Rembang, Process, Bumbang